Role of edaphic factors on VAM fungal colonization and Spore populations in certain tropical wild legumes - T., Muthukumar; K., Udaiyan; S., Manian (Universiti Putra Malaysia Press, 1994)
Four nodulating annual tropical wild legumes, viz., Alysicarpus monilifer, Desmodium triflorum, Indigofera linnaei and Tephrosia purpurea from three different regions in the Western Ghats ecosystem were investigated to assess their mycorrhizal status. The response ofvesicular-arbuscular mycorrhizal (VAM) root colonization and spore number to edaphicfactors such as soil moisture, pH and available Nand P was analysed. Though the spore number varied significantly both within and between sites, a uniformly high degree ofroot colonization was observed for all the plants in the present study. The spore number recorded was high, rangingfrom 15 to 165 spores gl soil. Spores of sixteen VAM fungal species belonging to Acaulospora, Glomus and Scutellospora were isolated from the rhizosphere soils. Soil moisture generally had a positive influence on VAM colonization and sporulation except in I. linnaei. The pH correlated negatively with root infection in I. linnaei and T. purpurea, but had no influence in the other two species. The effect of 2-pH on sporulation varied with host species and sites. No general correlation existed between available soil nutrients, root colonization and spore number but the influence ofNand P was counteractive on VAM infection. The present study indicates that the response of root colonization and spore number to edaphic factors is a localised rather than a generalised phenomenon.